Placental galectins regulate innate and adaptive immune responses in pregnancy - Oravecz, Orsolya; Romero, Roberto; Tóth, Eszter; Kapitány, Judit; Posta, Máté; Gallo, Dahiana M.; Rossi, Simona W.; Tarca, Adi L.; Erez, Offer; Papp, Zoltán; Matkó, János; Than, Nándor Gábor; et al. (Frontiers in Immunology, 2022)
Galectins are master regulators of maternal immune responses and placentation in pregnancy. Galectin-13 (gal-13) and galectin-14 (gal-14) are expressed solely by the placenta and contribute to maternal-fetal immune tolerance by inducing the apoptosis of activated T lymphocytes and the polarization of neutrophils toward an immune-regulatory phenotype. Furthermore, their decreased placental expression is associated with pregnancy complications, such as preeclampsia and miscarriage. Yet, our knowledge of the immunoregulatory role of placental galectins is incomplete. This study aimed to investigate the effects of recombinant gal-13 and gal-14 on cell viability, apoptosis, and cytokine production of peripheral blood mononuclear cells (PBMCs) and the signaling pathways involved. Herein, we show that gal-13 and gal-14 bind to the surface of non-activated PBMCs (monocytes, natural killer cells, B cells, T cells) and increase their viability while decreasing the rate of their apoptosis without promoting cell proliferation. We also demonstrate that gal-13 and gal-14 induce the production of interleukin (IL)-8, IL-10, and interferon gamma cytokines in a concentration-dependent manner in PBMCs. The parallel activation of Erk1/2, p38, and NF-ĸB signaling evidenced by kinase phosphorylation in PBMCs suggests the involvement of these pathways in the regulation of the galectin-affected immune cell functions. These findings provide further evidence on how placenta-specific galectins assist in the establishment and maintenance of a proper immune environment during healthy pregnancy.